Simultaneous polarization filtering and wavefront shaping enabled by localized polarization-selective interference - Jixiang Cai (Nature Portfolio, 2020)
Abstract The ability of simultaneous polarization filter and wavefront shaping is very important for many applications, especially for polarization imaging. However, traditional methods rely on complex combinations of bulky optical components, which not only hinder the miniaturization and integration but also reduce the efficiency and imaging quality. Metasurfaces have shown extraordinary electromagnetic properties to manipulate the amplitude, polarization, and wavefront. Unfortunately, multi-layer metasurfaces with complex fabrication are often required to realize complex functions. Here, a platform of monolayer all-dielectric metasurfaces is proposed to simultaneously achieve polarization filtering and wavefront shaping, based on the principle of local polarization-selective constructive or destructive interference. The transmission efficiency surpassing 0.75 and polarization extinction ratio exceeding 11.6 dB are achieved by the proposed metasurface at the wavelength of 10.6 μm. These results are comparable to those of multi-layer metasurfaces. Considering these good performances, this work may prove new ideas for the generation of complex optical field and find wide applications in polarization imaging.